Climate Safety: the Essence and Need for Financial Support (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Anthropogenic impact on the natural environment is investigated in the article; defined financial aspects of ensuring climate security and forming a climate policy; Climatic security has been found to be the protection of ecosystems and their associated forms of human life from global climate change and their consequences, climate risk – the extent to which this system is susceptible to the adverse effects of climate change and is unable to withstand negative impacts. climate change, including climate variability and extreme climatic phenomena. The main risks are: natural, man-made, and environmental. Сlimatic risks are manifested in the agricultural sector In Ukraine: loss of crops, changes in the periods of maturation of agricultural crops and increase their vulnerability to pests; in the field of water resources: violation of hydrodynamic regime and water balance of rivers; degradation of water resources; in the energy sector: the complication of the functioning of hydro-energy objects; in the area of public health: increasing the number of victims of heat stroke.It is proposed that, in order to realize the goals of the state policy, counteract climate change, ensure the development of a mechanism for financial support for its implementation. The financial mechanism for combating climate change and adaptation to such changes includes regulatory, informational and organizational support, the accumulation of financial methods and tools that provide the formation of financial resources to achieve the identified goals. The main sources of financing for the implementation of climate policy are state and local budgets, funds from international financial organizations, the Energy Efficiency Fund, and investment companies. It is expedient to apply mechanisms of co-financing with the participation of the state, local authorities, economic entities, households, international funds in the future.
Keywords: climate security, climatic risks, financial mechanism, financial support, financial resources.